2015
DOI: 10.1158/0008-5472.can-14-2435
|View full text |Cite
|
Sign up to set email alerts
|

Nitrostyrene Derivatives Act as RXRα Ligands to Inhibit TNFα Activation of NF-κB

Abstract: Retinoid X receptor alpha (RXRα) and its N-terminally truncated version - tRXRα are widely implicated in cancer development and represent intriguing targets for cancer prevention and treatment. Successful manipulation of RXRα and tRXRα requires the identification of their modulators that could produce therapeutic effects. Here we report that a class of nitrostyrene derivatives bind to RXRα by a unique mechanism, of which the nitro group of nitrostyrene derivatives and Cys432 of RXRα are required for binding. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Recent studies showed that RXRα binding to PML/RARα is absolutely required for the development of acute promeylocytic leukemia (APL) in transgenic mice [53][54][55], demonstrating the oncogenic potential of this protein when it acts inappropriately. Several groups have demonstrated that RXRα is proteolytically cleaved in cancer cells [23,45,51,[56][57][58][59][60], and our illustration that tRXRα could enhance TNFα activation of PI3K/AKT and NF-κB pathways revealed that aberration in RXRα signaling by limited proteolysis plays an active role in cancer development [28,29,[61][62][63][64][65].…”
Section: Rxrα and Cancermentioning
confidence: 55%
See 3 more Smart Citations
“…Recent studies showed that RXRα binding to PML/RARα is absolutely required for the development of acute promeylocytic leukemia (APL) in transgenic mice [53][54][55], demonstrating the oncogenic potential of this protein when it acts inappropriately. Several groups have demonstrated that RXRα is proteolytically cleaved in cancer cells [23,45,51,[56][57][58][59][60], and our illustration that tRXRα could enhance TNFα activation of PI3K/AKT and NF-κB pathways revealed that aberration in RXRα signaling by limited proteolysis plays an active role in cancer development [28,29,[61][62][63][64][65].…”
Section: Rxrα and Cancermentioning
confidence: 55%
“…This is supported by the observation that Sulindac and analogs inhibit the binding of tRXRα to p85α [29]. Similarly, inhibition of tRXRα-mediated activation of NF-κB survival pathway also leads to apoptosis [65]. These results demonstrate that inhibition of tRXRα-mediated activation of PI3K/AKT and NF-κB pathways could effectively shift TNFα signaling from survival to death.…”
Section: Trxrα and Apoptosismentioning
confidence: 66%
See 2 more Smart Citations
“…7 In addition, A-nitrostyrene inhibits gastric cancer cell proliferation, 11 and its derivatives suppress TNF>/NFJB signaling in a retinoid X receptor >Ydependent manner to induce breast cancer cell apoptosis. 12 Our previous work showed that 3 ¶-hydroxy-4 ¶-methoxy-A-methyl-A-nitrostyrene (CYT-Rx20)-induced apoptosis in breast cancer cells through reactive oxygen species (ROS)mediated MEK-ERK signaling. 13 However, to our knowledge, the biologic activities of CYT-Rx20 on cervical cancer cells have not been investigated.…”
mentioning
confidence: 99%